2014
DOI: 10.1007/s11916-014-0413-8
|View full text |Cite
|
Sign up to set email alerts
|

Licit and Illicit Drug Use in Cluster Headache

Abstract: Cluster headache patients seem to use more licit and illicit substances than the general population. The epidemiologic data supporting this is growing. We included the licit drugs in this review because their use seems to be driven by the same addiction mechanisms leading to illicit drug abuse. Some drugs may be used in an attempt to treat cluster headache, especially cocaine and hallucinogens. Drug exposure may also play a role in CH pathophysiology, as suggested by interesting data on tobacco use and second-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 79 publications
0
24
0
1
Order By: Relevance
“…Nicotine readily crosses the blood–brain barrier with uptake by passive diffusion and active transport by the choroid plexus. Within the brain, tritiated S‐nicotine binds to cortical, hippocampal, nigrostriatal, mesolimbic, thalamic, hypothalamic, midbrain, and brain stem receptors, with hypotheses that for certain headaches, nicotine central nervous system (CNS) action is direct, for example, in cluster at the hypothalamus . Nonetheless, in human studies and pain models, the effects of nicotine are often inconsistent and sometimes conflicting .…”
Section: Nicotine and Possible Pathophysiologic Associations With Heamentioning
confidence: 99%
See 4 more Smart Citations
“…Nicotine readily crosses the blood–brain barrier with uptake by passive diffusion and active transport by the choroid plexus. Within the brain, tritiated S‐nicotine binds to cortical, hippocampal, nigrostriatal, mesolimbic, thalamic, hypothalamic, midbrain, and brain stem receptors, with hypotheses that for certain headaches, nicotine central nervous system (CNS) action is direct, for example, in cluster at the hypothalamus . Nonetheless, in human studies and pain models, the effects of nicotine are often inconsistent and sometimes conflicting .…”
Section: Nicotine and Possible Pathophysiologic Associations With Heamentioning
confidence: 99%
“…More CH patients smoke than migraineurs, smoke more heavily, and use more substances . In a study of possible predictive factors in the evolution of episodic to chronic CH, Torelli et al concluded cigarette‐smoking rates and causality still cannot be established with certainty .…”
Section: Clustermentioning
confidence: 99%
See 3 more Smart Citations